Communication for business professionals - Simon, David; Grimes, Michelle; Roch, Shauna; BC Open Textbook Project; BCcampus (eCampusOntario, 2018)
"This books provides a comprehensive, integrated approach to the study and application of written and oral business communication to serve both student and professor. The text includes a number of features such as learning objectives, exercises, real world examples, key terms, and post-chapter assessments.This text is adapted from Business Communication for Success. This 2018 adaptation has significantly reduced the size and scope of the original publication and added Canadian examples. This open textbook is designed in 12 chapters featuring a spectrum of current and relevant Canadian business communication topics."--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Description based on online resource; title from PDF title page (viewed on September 19, 2018).
Keywords: Business communication -- Textbooks; Electronic books